Nilai Moral dalam Novel Charlie and The Great Glass Elevator Karya Roald Dahl - Fauzi Abdullah Al Zein (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
The entitled of research is Moral Value in the novel Charlie and the Great Glass Elevator. The purposes of the research are to description of the moral values of human-human relations and to describe the form of delivery of moral values contained in the Novel. This research uses descriptive qualitative method according with Pragmatic approach method. The data were colleted trough Baca and Catat techniques. The step to data analysis there is: data reduce, data presentation and conclusion. The results of the research, to describe the moral value of human relations with humans, there is: (1) value of caring for other, (2) love value, (3) honesty value, (4) value respect, (5) value responbility, (6) value reminding each other, (6) value of mutual trust. The form of delivery of moral values in this study has two specifications, namely the delivery of direct moral values and the delivery of indirect moral values. The delivery of moral values directly through the characters, and the delivery of indirect moral values have the form of delivery in the form of events and conflicts.